2020
DOI: 10.1155/2020/1057570
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hypertension and Metabolic Syndrome on Nitrosative Stress and Glutathione Metabolism in Patients with Morbid Obesity

Abstract: In this pathbreaking study, we evaluated nitrosative stress in morbidly obese patients with and without metabolic syndrome. 62 women with class 3 obesity (BMI>40 kg/m2) were divided into three subgroups: obese patients (OB), obese patients with hypertension (OB+HYP), and obese patients with metabolic syndrome (OB+MS). In comparison to the lean patients, OB had increased levels of serum myeloperoxidase (MPO), plasma nitric oxide (NO), S-nitrosothiols, and peroxynitrite (ONOO−), as well as nitrotyrosine, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 57 publications
2
24
0
1
Order By: Relevance
“…This situation is called redox imbalance and leads to oxidative damage to cellular biomolecules [2]. Indeed, ROS are not only proven to play a crucial role in many physiological processes [3,4], but they are also a vital factor in the pathogenesis of many diseases like obesity [5,6], insulin resistance [7,8], hypertension [9,10], and chronic heart failure [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is called redox imbalance and leads to oxidative damage to cellular biomolecules [2]. Indeed, ROS are not only proven to play a crucial role in many physiological processes [3,4], but they are also a vital factor in the pathogenesis of many diseases like obesity [5,6], insulin resistance [7,8], hypertension [9,10], and chronic heart failure [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also reported that glycation of vascular proteins plays a vital role in hypertension development [5,13,14]. Interestingly, higher circulating levels of advanced glycation end products (AGE) correlate with increased arterial stiffness [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation may be a constant oxidative stress as suggested by our experiment. As many studies have confirmed the key role of redox imbalance in obesity, insulin resistance, and diabetes pathophysiology [ 9 , 10 , 70 ], metabolic disorders in phaeochromocytoma may result from disturbances in antioxidant barrier and intensification of oxidative stress. This may be indicated by the positive correlation between plasma glucose and urinary MDA levels, as well as between metanephrine and BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of adrenal tumors requires complex studies; so in our study, we also decided to assess the markers of oxidative stress in the serum/plasma and urine as a material for research in an easily accessible and minimally invasive manner. It has recently been emphasized that oxidative stress plays a critical role in the pathogenesis of various diseases such as neurodegenerative diseases [ 74 , 75 ], insulin resistance [ 76 ], diabetes [ 77 , 78 ], hypertension [ 79 , 80 ], metabolic syndrome [ 10 , 81 ], stroke [ 82 , 83 ], and cancer [ 84 , 85 ]. Thus, we compared whether antioxidants/oxidation products can differentiate between patients with adrenal masses (incidentaloma, pheochromocytoma, and Cushing/Conn adenoma) as well as healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A severe course of COVID-19 is a result of both the direct cytolytic effects of SARS-CoV-2 and the imbalanced production of reactive oxygen species by the cell resulting in extensive inflammation and tissue destruction ( Schönrich et al, 2020 ). GSH not only sweeps away oxygen free radicals, but also regenerates other oxidised antioxidants and takes part in the repair of oxidative stress-damaged biomolecules ( Choromańska et al, 2020 ). It has been reported that erythrocyte GSH was significantly lower in patients who received 100 mg/kg/day of paracetamol compared with patients who received paracetamol at a dose of 50 mg/kg/day and those who did not receive paracetamol ( Kozer et al, 2003 ).…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%